Laparoscopic left and right adrenalectomy from an anterior approach – is there any difference? Outcomes in 176 consecutive patients - Lukas Kokorak; Marek Soltes; Peter Vladovic; Lubomir Marko (Videosurgery and Other Miniinvasive Techniques)
Introduction : Traditionally, in open surgery, right adrenalectomy is considered technically more demanding than its left-sided counterpart. This belief is supposed to be attributable mainly to different anatomic characteristics of the adrenal veins. Whether this opinion is also correct for laparoscopic adrenalectomy remains elusive. Aim : To compare the outcomes of left versus right laparoscopic adrenalectomy from an anterior approach. Material and methods: Retrospective statistical analysis of a prospectively compiled database of consecutive patients undergoing laparoscopic adrenalectomy in a single center with focus on potential differences in the left- versus right-sided procedure in terms of demographic parameters, tumor size, operating time, occurrence of serious intraoperative complications, conversion, length of hospital stay and re-operation rate. Results: One hundred seventy-six patients underwent elective laparoscopic adrenalectomy – 80 left-sided (45.45%) and 96 right-sided (54.55%). No significant difference was found between the groups in terms of age (54.09 ±11.2 vs. 56.27 ±11.6; p = 0.2), tumor size (3.39 ±1.86 vs. 3.26 ±1.66; p = 0.64), operating time (71.84 ±22.33 vs. 72.06 ±30.99; p = 0.95), occurrence of serious intraoperative complications (7.5% vs. 10.4%; p = 0.5), conversion (1.25% vs. 1.04%; p = 0.9), length of hospital stay (4.52 ±1.30 vs. 4.37 ±1.91; p = 0.55) or reoperation rate (5% vs. 1%; p = 0.11). There was no mortality. Conclusions : No significant difference was found between the left and right laparoscopic adrenalectomy in terms of operating time, occurrence of serious intraoperative complications, conversion rate or postoperative outcome. Therefore, the opinion that the right-sided procedure is more difficult does not seem to be justified for laparoscopic adrenalectomy from the anterior approach.